Odpowiedzi

2010-03-24T14:32:39+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9/3
x=3

c) 10=4-2x
2x=4-10
2x=6/2
x=3

d) -(2x-1)=x
-2x+1=x
-2x-x=-1
-3x=-1/(-3)
x=0,3

e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-1t=7/(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0






  • Użytkownik Zadane
2010-03-24T14:37:10+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9/3
x=3

c) 10=4-2x
2x=4-10
2x=6/2
x=3

d) -(2x-1)=x
-2x+1=x
-2x-x=-1
-3x=-1/(-3)
x=0,3

e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-1t=7/(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
Najlepsza Odpowiedź!
2010-03-24T15:36:52+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9
x=3

c) 10=4-2x
10-4=-2x
6=-2x
x=-3

d) -(2x-1)=x
-2x+1=x
1=x+2x
1=3x
x=1/3

e) 2(x+1)=x
2x+2=x
2=x-2x
2=-x
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-1
0=0